Physicochemical, phenolic and productivity parameters of the Tannat variety under soil cover associated with defoliation (Research, Society and Development, 2023)
Due to the great search for quality of the grapes, researchers and producers intensify the discovery of new technologies and managements. As defoliation is a common technique in vineyards, inorganic soil cover is an alternative to be combined, in order to improve the physical and chemical characteristics of the berries, reflecting on the quality of the must and wine. For this reason, this work aimed to evaluate the effects of an inorganic material as a soil cover together with the defoliation of plants on fruit yield, quality of must and quality of wine. The treatments with white plastic canvas arranged in the period of fruiting and partial defoliation, in the 2020 harvest, were worked out. We can conclude from the results that the treatment with soil cover without defoliation had greater mass of the bunches. The other variables of the must and wine did not show statistical difference. Therefore, for these conditions, defoliation had no influence on treatments, and ground cover can be an alternative to improve the physical characteristics of the Tannat grape.